Determinasi Responsibilitas Tatakelola Keuangan Desa - Kuras Purba; Rintan Br. Saragih; Sahala Purba (Universitas Muhammadiyah Malang, 2022)
This research intends to examine and analyze the competence of human resources, community involvement, supervision, and utilization of information technology that affect the Responsibilities of Village Financial Management in the Brand District of Karo Regency. This type of research is quantitative research and uses primary data. The data collection model used is a questionnaire. The analytical model used in this research is descriptive analysis and multiple linear regression. This research was used in 12 villages in the Brand District, and in each village 4 respondents were obtained, namely the Village Head, Village Secretary, Head of Finance, and one BPD person, so that the total number of respondents was 48 people. This research was conducted in April – May 2021. The results of this research show that human resource skills, community involvement, and technology utilization have a positive and significant correlation to Village Financial Governance Responsibility, while supervision has a negative and significant correlation to Village Financial Governance Responsibility. The contribution of this research is that the existence of human resource skills, community involvement, supervision, and utilization of technology can strengthen the responsibility of village financial governance throughout Indonesia, especially in villages located in the village of Brand District.